HtrA‐dependent adherence and invasion of Campylobacter jejuni in human vs avian cells. (1st April 2020) - Simson, D.; Boehm, M.; Backert, S.
Abstract: The aim of this study was to investigate whether HtrA is responsible for differences in adherence and invasion of Campylobacter jejuni towards human and chicken cell lines. Gentamicin protection assays were performed with either human Caco‐2 or chicken 2G4 cells using C. jejuni strain NCTC11168 to compare the adhesion and invasion rates towards these two cell types. The results revealed significant differences in the adhesion and invasion rates between the human and avian cells. Deletion of the Campylobacter htrA gene, coding for the dual function of serine protease and chaperonin with a role in pathogenesis, led to a reduction of the rates in both cell lines. Using a single‐amino acid substitution mutant (Δ htrA/htrA S197A ) that lacked protease activity, but retained chaperonin activity, we show that the first is involved in the invasion of human Caco‐2 and chicken 2G4 cells, whereas the latter mutant invaded at lower levels. Adherence towards the chicken cells is higher than towards Caco‐2 cells and this is also dependent on HtrA. Together, these data suggest that the proteolytic activity of HtrA is involved in the difference in host response of C. jejuni towards human and chicken‐derived cells. Significance and Impact of the Study: Campylobacter jejuni is the main cause for bacterial foodborne enterocolitis worldwide. While colonization of the human intestine can lead to severe problems, avian hosts – as the major source of infection – remain unaffected by the bacteria. We showed that the bacterial serine protease and chaperonin HtrA are involved in adhesion and invasion in both species and not responsible for the discrepancy of virulence between the different hosts. In future, HtrA might act as a target for inhibitors to avoid or eradicate colonization in chickens as a less problematic alternative to antibiotics in commercial livestock breeding.